LEVERAGING CUSTOMER JOURNEY TO INCREASE RESIDENTIAL ROOFTOP SOLAR PV USERS: THE CASE OF LENSOLAR - Kusuma Nagari, Dina
Indonesia is targeted to increase the use of renewable energy to 23% by 2025. The highest potential of new and renewable energy comes from solar energy for about 207,8 GWp due to the abundance of year-round sunshine in Indonesia. This creates a huge market potential for rooftop solar system. Currently, the trend also shows a rapid growth in photovoltaic technology and with the wider distribution of information, public interest is also increasing. However, according to the technology adoption life cycle, the market of rooftop solar product in Indonesia is still in the early adopters since the number is growing yet still very small. Since it is a high technology product that is still unpopular among society, it may face some challenges so that it needs marketing model to increase the number of its users from the mainstream market and therefore increasing the sales for the company. One of the companies that provides rooftop solar is PT Len Industri (Persero) through its subsidiary, PT Surya Energi Indotama/PT SEI under the brand named LenSOLAR. The brand was launched in 2019 and targeted for residential and business customers. Therefore, it needs marketing initiatives to increase its users and the revenue for the company. To increase the number of users and for the customers to initiate purchase, they are usually going into customer journey starting from awareness, appeal, ask, then act (purchase). The objectives of the research in this final project are to understand the customer journey of rooftop solar product in general, the customer journey of LenSOLAR as rooftop solar brand, and to identify the marketing initiatives to increase LenSOLAR users according to its customer journey to enter early majority/mainstream market. In order to achieve the objectives, the survey was done along with internal and external analysis and the solution was formulated using high-tech marketing model and content marketing framework.